Pemanfaatan Bahan Lokal dalam Pakan Ikan oleh Petani Tambak Desa Reuleut Timur, Aceh Utara - Rachmawati Rusydi; Mainisa; Salamah; Riani (JPM: Jurnal Pengabdian Masyarakat, 2022)
The high price of commercial feed causes higher production costs. The problem was experienced by fish farmers, including the groups of pond farmers in East Releut Village, North Aceh. The purpose of this activity is to improve the pond farmer's skills by developing artificial fish feed made from local raw materials using Moringa leaf flour. This service activity uses an educative, participatory, and persuasive method approach. Also, the procedures consist of several stages, that are socialization about artificial fish feed made from local raw materials, socialization about the introduction of various local raw materials that have the potential to be used as feed ingredients, socialization about manufacturing technology fish feed, training in the stages of making fish feed, and marketing training for artificial fish feed made from local raw materials. The socialization and training on the process of artificial feed also motivate pond farmers to produce fish feed made from local raw materials. The participants were very satisfied on the knowledge/information (64,58%), the explanation of knowledge (72,22%), and the whole activity (63,89%), and satisfied on discussion process (58,33%). Participants hoped that developing artificial feed products, could reduce the cost of production